Introduction: China and International Development: Challenges and Opportunities. (15th July 2014) - Gu, Jing; Li, Xiaoyun; Bloom, Gerald; Zhang, Xiulan
Abstract In parallel to its domestic economic boom, China has also been growing as an international actor and as a 'Rising Power' in global development. This introduction outlines the need for further understanding of China's own development experience, its increasing involvement in development activities in low‐ and middle‐income countries, and its growing engagement in global governance structures. The articles highlighted contribute valuable expertise and insight from both Chinese and non‐Chinese perspectives, to map the shifting landscape of China's engagement in global development, and contribute to mutual understanding between traditional donors and rising powers in development cooperation.